Salinity-mediated limitation of asexual reproduction in the colonial ascidian Polyandrocarpa zorritensis - Tobias-Santos, Vitoria; Andreoni-Pham, Rita; El Gharbi, Dany; Lebel, Marie; Tiozzo, Stefano; Alié, Alexandre (Frontiers in Ecology and Evolution, 2024)
Ascidians are among the most common invasive marine invertebrates worldwide.Many species of non-indigenous ascidians (NIAs) have successfully colonized the Mediterranean Sea, notably within anthropized coastal lagoons and harbors. Although invasive species are generally characterized by their broad ecological tolerance, different ascidian species exhibit varied responses to biotic and abiotic environmental stressors, including temperature and salinity. Acquiring a better understanding about of the impact of such parameters on ascidian life history is crucial for predicting the invasive potential of NIAs. In this study, we investigated the impact of various salinities on the reproduction of the colonial ascidian Polyandorcarpa zorritensis, a species indigenous to Peru and a thriving invader. P. zorritensis undergoes asexual reproduction via a peculiar form of budding named vasal budding and produces resistant spherules, which likely facilitated its dissemination over long distances.Despite its widespread distribution along the Pacific and Atlantic coasts, it is only found in a few Mediterranean coastal areas with a low salinity. We tested the impact of different salinity conditions on the sexual and asexual reproduction rates of P. zorritensis in a controlled laboratory setting. Our experiments showed that the rate of asexual reproduction in colonies bred at 29 or 36 ppt salinity levels, corresponding to the natural range inhabited by P. zorritensis, was higher than those grown in 40 ppt salinity, commonly found in Mediterranean marinas and harbors. The results suggest that, although P. zorritensis has been present in the Mediterranean for several decades, its potential for invasion could be constrained by an intolerance to high salinity.